Dehydroepiandrosterone: a neuroactive steroid - Stárka, Luboslav; Dušková, Michaela; Hill, Martin (The Journal of steroid biochemistry and molecular biology, 2015)
Dehydroepiandrosterone (DHEA) and its sulfate bound form (DHEAS) are important steroids of mainly adrenal origin. They are produced also in gonads and in the brain. Dehydroepiandrosterone easily crosses the brain-blood barrier and in part is also produced locally in the brain tissue. In the brain, DHEA exerts its effects after conversion to either testosterone and dihydrotestosterone or estradiol via androgen and estrogen receptors present in the most parts of the human brain, through mainly non-genomic mechanisms, or eventually indirectly via the effects of its metabolites formed locally in the brain. As a neuroactive hormone, DHEA in co-operation with other hormones and transmitters significantly affects some aspects of human mood, and modifies some features of human emotions and behavior. It has been reported that its administration can increase feelings of well-being and is useful in ameliorating atypical depressive disorders. It has neuroprotective and antiglucocorticoid activity and modifies immune reactions, and some authors have also reported its role in degenerative brain diseases. Here we present a short overview of the possible actions of dehydroepiandrosterone and its sulfate in the brain, calling attention to various mechanisms of their action as neurosteroids and to prospects for the knowledge of their role in brain disorders.
Keywords: Steroids; Dehydroepiandrosterone Sulfate; Androgens; Dehydroepiandrosterone; androgeny; mužské pohlaví; Central Nervous System; Dihydrotestosterone; Testosterone; Dehydroepiandrosterone, Dehydroepiandrosterone sulfate, Neurosteroid, Brain, 7-Hydroxy-dehydroepiandrosterone; mozek; nadledviny; dehydroepiandrosteronsulfát; testosteron; Gonads; steroidy; gonády; kyslík; centrální nervový systém; Brain; zvířata; Humans; Adrenal Glands; dehydroepiandrosteron; Oxygen; dihydrotestosteron; lidé; Male; Animals